POTENSI TINGKAT PERTUMBUHAN TANAMAN AREN (Arenga pinnata MERR.) DI KABUPATEN HULU SUNGAI TENGAH KALIMANTAN SELATAN - Dina Naemah; Damaris Payung; Fauzi Karni (Jurnal Hutan Tropis, 2022)
Arenga pinnata is a plant that has potential for the community as a source of income that can improve the welfare of the community because most of them get a source of income from processing this plant. Almost all parts of the sugar palm plant can be utilized, from the roots to the male flower bunches that can produce sap.Plant structure is the organization of individuals in space and composition is the arrangement of forest stands that includes the number of species or the number of individuals. Composition means also studying the distribution of a plant species based on density, frequency and dominance value. Vegetation structure is the result of spatial planning by stand components or plant communities in a community both vertically and horizontally. The purpose of this study was to determine the potential distribution of sugar palm growth rates in one of the districts in South Kalimantan, Hulu Sungai Tengah. The analysis was carried out by calculating the significant value index (INP) based on the values of Density, Frequency and Dominance. Data were collected using the plotted path method. The results showed that the density of sugar palm seedlings was very large, with an average of 13,055 seedlings/Ha (INP: 200%), the average pole density was 217 stems/Ha and the tree level averaged 90 trees/Ha. The number of panicles, which is the part that is used as raw material for making brown sugar, amounts to an average of 90 panicles/ha.